Sleep in athletes undertaking protocols of exposure to nocturnal simulated altitude at 2650 m - Kinsman, T. A.; Gore, C. J.; Hahn, A. G.; Hopkins, W. G.; Hawley, J. A.; McKenna, M. J.; Clark, S. A.; Aughey, R. J.; Townsend, N. E.; Chow, C. M. (Journal of Science and Medicine in Sport, 2005)
A popular method to attempt to enhance performance is for athletes to sleep at natural or simulated moderate altitude (SMA) when training daily near sea level. Based on our previous observation of periodic breathing in athletes sleeping at SMA, we hypothesised that athletes' sleep quality would also suffer with hypoxia. Using two typical protocols of nocturnal SMA (2650 m), we examined the effect on the sleep physiology of 14 male endurance-trained athletes. The selected protocols were Consecutive (15 successive exposure nights) and Intermittent (3x 5 successive exposure nights, interspersed with 2 normoxic nights) and athletes were randomly assigned to follow either one. We monitored sleep for two successive nights under baseline conditions (B; normoxia, 600 m) and then at weekly intervals (nights 1, 8 and 15 (N1, N8 and N15, respectively)) of the protocols. Since there was no significant difference in response between the protocols being followed (based on n=7, for each group) we are unable to support a preference for either one, although the likelihood of a Type II error must be acknowledged. For all athletes (n=14), respiratory disturbance and arousal responses between B and N1, although large in magnitude, were highly individual and not statistically significant. However, SpO2 decreased at N1 versus B (p<0.001) and remained lower on N8 (p<0.001) and N15 (p<0.001), not returning to baseline level. Compared to B, arousals were more frequent on N8 (p=0.02) and N15 (p=0.01). The percent of rapid eye movement sleep (REM) increased from N1 to N8 (p=0.03) and N15 (p=0.01). Overall, sleeping at 2650 m causes sleep disturbance in susceptible athletes, yet there was some improvement in REM sleep over the study duration.